Short stories : nuove forme di narrazione nell'arte contemporanea - Play - Artemio; Avveduti, Sergia; Bertocchi, Davide; Bonacossa, Ilaria; Bookchin, Natalie; Bruguera, Tania; Caravaggio, Gianni; Churi, Maja; Corbetta, Caroline; Cornyn, Alison; Crowe, Nick; Curto, Guido; et al. (Milano : Comune di Milano, 2001)
Arias Gaviria, Fernando ; Artemio ; Bertocchi, Davide ; Bonillas, Iñaki ; Bookchin, Natalie ; Bruguera, Tania ; Churi, Maja ; Cornyn, Alison ; Johnson, Sue ; Crowe, Nick ; Escobar, Dario ; Gabinete Ordo Amoris ; Geers, Kendell ; Kumjim, Prapon Joe ; Maloberti, Marcello ; Mocellin, Ottonella ; Ozkaya, Serkan ; Özmen, Sener ; Paci, Adrian ; Rasjarmreansook, Araya ; Restrepo, José Alejandro ; Sangar, Bülent ; Vari, Minnette ; Viel, Cesare ; Villagomez, Lourdes Aimée ; Weerasethakul, Apichatpong ; Xhafa, Sislej ; Avveduti, Sergia ; Berti, Simone ; Caravaggio, Gianni ; Ciraci, Sarah ; Cuoghi, Roberto ; Galegati, Stefania ; Golia, Piero ; Ligorio, Deborah ; Perrone, Diego ; Pivi, Paola ; Simeone, Marcello
ind. tent., gr. tent., bibliog. p. 260-275, p. 324-331
Italiaans & Engels
Play, 27.03 - 29.04.2001 ; Short stories, 28.03 - 29.04.2001, La Fabbrica del Vapore Milano, Openspace Milano, Comune di Milano
boek